Using FTIR Analysis to Investigate the Mineralogical Composition of Ultisolsa Alfisol in Southeast East Sulawesi, Indonesia - Rosliana Eso; Tufaila Tufaila; Arman Arman (Department of Physics, Sebelas Maret University, 2025)
This study aims to investigate the mineralogical composition of Ultisols and Alfisols using the X-ray diffraction (XRD) analytical technique and FTIR analysis to provide fundamental information on these soil types. Thirty samples of Ultisols and Alfisols were collected from six selected sites with different profiles (i.e., Profile 1, Profile 2, and Profile 3) where these soils occur on limestone parent material. We used the Kjeldahl method to determine total nitrogen, a soil pH meter to measure pH, and the X-ray fluorescence (XRF) method to analyze chemical elements. Additionally, XRD in conjunction with FTIR spectroscopy was used to examine the mineralogical composition of both soil types.The average total nitrogen content across all profiles ranged from 0.1% to 0.35% for Ultisols and from 0.1% to 0.92% for Alfisols. The soil pH indicated an alkaline reaction, ranging from 4.5 to 5.3 for Ultisols and from 4.8 to 6.2 for Alfisols. Chemical element content obtained from oxides in all profiles included Si, Al, Fe, Mg, Ti, Ca, S, Na, K, P, Mn, Ni, Co, and Cr. Dominant Si trends, consistently increasing upward on both Ultisol and Alfisol sites, indicated significant soil development in the study area. The diffraction pattern graphics of topsoil from all profiles identified a 100% Silicon oxide quartz low (SiO2) phase with the trigonal (hexagonal axes) crystal system. FTIR spectroscopy analysis showed progressive kaolinization in all Alfisol samples. In contrast, Ultisol Profile 1 expressed montmorillonite, while Profiles 2 and 3 attributed to kaolinite. FTIR results consistently